2023
DOI: 10.1098/rsos.230316
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of epidemiological parameters and ascertainment rate from early transmission of COVID-19 across Africa

Qing Han,
Nicola Bragazzi,
Ali Asgary
et al.

Abstract: Country reported case counts suggested a slow spread of SARS-CoV-2 in the initial phase of the COVID-19 pandemic in Africa. Owing to inadequate public awareness, unestablished monitoring practices, limited testing and stigmas, there might exist extensive under-ascertainment of the true number of cases, especially at the beginning of the novel epidemic. We developed a compartmentalized epidemiological model to track the early epidemics in 54 African countries. Data on the reported cumulative number of cases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…It is important to underscore that the estimated basic and time-varying reproduction numbers in this study align closely with findings from other research. Notably, early pandemic research studies in Chad ( ), Central Afican African Republic ( ), Congo( ), Tanzania( ), Angola( ), Malawi( ) and Mozambique( ) by Han et al [ 23 ], employing similar methodologies, yielded estimates that were consistent or in close agreement with our basic reproduction estimates (see Table 1 ). In comparison to our study, very close estimates of the basic reproduction were also observed in Ivory Coast ( ), Ghana ( ), Kenya, ( ), and Nigeria ( ) from a study conducted by Oshinubi et al [ 24 ] and Demongeot et al [ 25 ].…”
Section: Resultssupporting
confidence: 85%
“…It is important to underscore that the estimated basic and time-varying reproduction numbers in this study align closely with findings from other research. Notably, early pandemic research studies in Chad ( ), Central Afican African Republic ( ), Congo( ), Tanzania( ), Angola( ), Malawi( ) and Mozambique( ) by Han et al [ 23 ], employing similar methodologies, yielded estimates that were consistent or in close agreement with our basic reproduction estimates (see Table 1 ). In comparison to our study, very close estimates of the basic reproduction were also observed in Ivory Coast ( ), Ghana ( ), Kenya, ( ), and Nigeria ( ) from a study conducted by Oshinubi et al [ 24 ] and Demongeot et al [ 25 ].…”
Section: Resultssupporting
confidence: 85%
“…The ascertainment rate, α, estimates were very low for Mozambique and Zimbabwe provinces, matching our prior assumption. Our estimates in both countries is in line with the studies by Han et al [18] and Evans et al [17]. This indicates that the majority of infections were never documented as cases; by extension, many severe cases requiring hospitalization or resulting in death may have been missed due to limited access to healthcare and testing facilities.…”
Section: Zimbabwe Parameter Estimatessupporting
confidence: 91%
“…The initial prior range of α i = [0.004 − 0.1] (which is low, corresponding to a maximum of one reported case for every ten infected) was motivated by the study of Han et al [18], which estimated an overall daily report rate (ascertainment rate) ranging from α = [0.0002 − 0.3], among all African countries. Furthermore, the study by Evans et al [17] highlighted that the lower-than-expected case burdens in Madagascar were explained solely by detection rates of 0.1-1% (or α = [0.001 − 0.01]).…”
Section: Initial Priorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WHO estimates that only one in seven cases was being detected in Africa ( 8 ), highlighting a substantial gap in data accuracy and completeness. Our previous investigation into the early phase of the COVID-19 outbreak across 54 African nations also revealed a significant under-reporting trend ( 9 ). Specifically, an average of only about 5.37% of all COVID-19 cases was duly reported.…”
Section: Introductionmentioning
confidence: 93%